Benchmarking of Research Management of Universidad Nacional Daniel Alcides Carrión - Peru and Universidad Pedagógica Nacional - Colombia - Carhuaricra Meza, Julio César (2019)
Benchmarking is “the systematic process of investigating, identifying, comparing and learning from the best practices of other organizations, whether they are in the same sector or not. Orderly analyzing the set of factors that affect their success, learning from their achievements and applying them in our own improvement processes” (Manene, 2011). This methodological proposal has been applied in the present study. A SWOT analysis has been carried out and then internal/external improvement differences have been sought based on comparative evaluations that focus on the weak points found to proceed to possible areas forimprovement. Allthis, within theframework of the internship in“training in research management” (UNDAC, 2017). This academic experience has been carried out from August 28 to September 01, 2017 at the Universidad Pedagógica Nacional de Bogotá - Colombia. In this event, “26 teachers from School of Education Sciences of Universidad Nacional Daniel Alcides Carrión de Pasco - Perú” (UNDAC, 2017) Objective. To identify, compare, learn and creatively apply the best practices in teacher training and basically in research management developed by Universidad Pedagógica Nacional de Bogotá - Colombia. Higher Education Institution that has 1,049 teachers and 11,092 students. In addition, it is considered “the best university in the country in teacher training, as it is also important in social and pedagogical research tasks with a critical character” (Universidad Pedagógica Nacional de Colombia, 2017). It also stands out for its teaching and student teams dedicated to research that is financially sponsored by Colciencias, through the Research Center. This organization articulates the administrative and academic part of research projects and publications of Indexed Journals, and it is complemented by cultural activities.